Collection Based Storyline Developer in Pekanbaru's Sang Nila Utama Museum - Supitri Romdania, Sri; Isjoni; Suroyo (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research aims to develop a media display in the form of a video storyline about historical collections at the Sang Nila Utama Pekanbaru Museum. Storyline is a storyline that is usually made in the form of written work, animation or it can also be in the form of a movie/video that tells a clear and directed story. This type of research is Research and Development. The results showed that the development of istoric-based Storyline in the Museum was 88% or with a very good category while for the material was 95% or very good category. the results of this study indicate that this Storyline can be applied to the Sang Nila Utama Museum.